Korean students' English language proficiency and its relationships to affective factors - Eunyoung Park (2006)
This study attempted to find out and understand the younger Korean students' English language learning process and learning success in the Philippines. It tried to determine the relationships of affective factors such as the level of anxiety, self-esteem and motivation, and their language proficiency from the aspects of gender, age, grade level, length of stay in the Philippines and their mode of residence. Chosen participants were 30 Korean students studying at Colegio de San Agustin in Makati, Metro Manila,The study used both correlational research and descriptive research. The instruments administered were the foreign Language Classroom Anxiety scale, Motivational Measure, Self-esteem Scale and the Comprehensive English Language Test. It was concluded that younger Korean students' language proficiency in English has a positive relationships with their length of stay in the Philippines.
"August 2006."
Thesis (M.A. Education : Language Education)--University of the Philippines Diliman.
Keywords: English language -- Grammar -- Study and teaching -- Philippines; English language -- Study and teaching (Elementary) -- Korean; English language -- Study and teaching (Elementary) -- Philippines -- Psychological aspects